A MODEL FOR PROMOTING AND PRESERVING THE WISDOM OF USING MEDICINAL PLANTS TO ENHANCEMAE KLA’S GRASSROOTS ECONOMY KHLONG HOI KHONG SUBDISTRICT KHLONG HOI KHONG DISTRICT, SONGKHLA PROVINCE - ., Phrakru Wiradhammachot; ., Phrakru Sittisutakorn Siddhimethi; Chimhad, Pairat; Ruknuiy, Prasit; Mueanjan, Wanida (Journal of MCU Nakhondhat, 2024)
The objectives of this research article are to 1) Explore the general conditions, problems, obstacles, and needs for medicinal plants from local wisdom in order to raise the level of the grassroots economy in communities in Songkhla Province, 2) To promote the cultivation and production of medicinal plants with the participation of the community in order to improve the grassroots economy of Ban Mae Kla. Khlong Hoi Khong Subdistrict Khlong Hoi Khong District, Songkhla Province and 3) To present a model for promoting the conservation of wisdom, use, and cultivation of medicinal plants to enhance the grassroots economy in Songkhla Province. This qualitative research used in-depth interviews with 25 people. Key informants include Government representative groups such as district agriculture, subdistrict agriculture, herbal expert groups, folk philosophers, Subdistrict doctors, local doctors, groups of herbal growers, and groups of people who bring herbs to use. Data analysis techniques were used inductively and presented descriptively. The research results found that 1) The general condition of the Ban Mae Kla community The area is ready to grow medicinal plants. But rubber cultivation is the main occupation of farmers. 2) Promote the cultivation and production of medicinal plants. The planting area has been increased with community participation. There are enough herbs to enter the production system. Wat Prang Kaew is the main leader in driving the promotion of planting. Create an herbal breeding bed within the temple and distribute the plants. and 3) A model for promoting the conservation of wisdom, use, and cultivation of medicinal plants to enhance the grassroots economy in Songkhla Province. Applying the principles of a sufficiency economy, herbs can make money and be self-reliant. Take on the role of community leader by making it visible from the upstream steps. Midstream and downstream. To summarize for children and grandchildren to inherit wisdom in the future.